The Effect Of Tax Planning, Deffered Tax Expense, Deffered Tax Asset and Tax Avoidance On Earnings Management - Hanifah, Nur Fadilah; Abukosim, Abukosim; Kesuma, Nilam (Dinasti Research, 2025)
This study aims to examine the impact of tax planning, deferred tax expense, deferred tax asset and tax avoidance on earnings management. The population for this research consists of LQ45 companies listed on the Indonesia Stock Exchange between 2019 and 2023. A total of 130 samples were selected using the purposive sampling method. The data analysis was conducted using multiple linear regression with SPSS 27. The findings indicate that tax planning, deferred tax expense and tax avoidance do not affect on earnings management, while deferred tax assets have a positive effect on earnings management.